(3Yde GdSGYGJ hGdYed HgGs - (3QVhGf Hf eMqeO Hf Ydj Hf QSJe, aNQ GdOjf GdNQGSGfj, GHf GdSGYGJj,J (B618 (3g` s ((3GdbGgQI s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg JYGdi Ydi fYeGFg hGdUdGI hGdSdGe Ydi eMeO Udi Gddg Ydjg hYdi Bdg NjQ CfHjGFg s
(3BNQgG (B:s
(3Ydi UGMHgG GaVd GdSdGe hcJH QVhGf Hf eMeO GdNQGSGfi gcPG cGf ecJhHkGai GdfSNI GdJi HNW eUfagG s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B27 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B166s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B473 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B866 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B175 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdUfGYI hGdCWYeIs